Early weaning and concentrate supplementation on body condition score of Mecehri ewes and lambs - Kumar, R Santosh; Ramesh, V; Kumar, K Siva; Thiruvenkadan, A K (Indian Journal of Animal Production and Management, 2018)
This study was carried out on Mecheri lambs and ewes at Mecheri Sheep Research Station. A total of 72 Mecheri lambs were divided into three treatment i.e., weaned at 90 days (T1), 75 days (T2) and 60 days (T3) with 24 lambs in each treatment. Each treatment was again divided into two groups, based on the concentrate supplementation level i.e., 1 and 1.5% of body weight and all lambs were maintained under semi-intensive system of management. The body condition score for lambs were taken fortnight interval up to 7 months of age and ewes body condition score was recorded at different breeding stages (lambing, weaning, mating, midgestation and subsequent lambing). The results revealed that lambs body condition score was not influenced by weaning ages but level of concentrate feeding had greater influence on body condition score of lambs. Lambs fed with 1.5% concentrate supplement group had significantly higher body condition score compared to 1.0% supplementation. Ewe body condition score observed during different reproductive stages and concluded that weaning age of lambs did not have any influence on body condition score of ewes within period but it differed between reproductive stages. BCS of ewes was lower during weaning and higher during mid gestation and at lambing.